The Effectiveness Of Multimedia In Teaching Writing To Students With Different Learning Styles - Manikowati, Manikowati; Linggar Bharati, Dwi Anggani (English Education Journal, 2017)
This research was to analyze the effectiveness of Interactive Multimedia Instructions (IMIs) in the format of game (GIMI) and in the format of tutorial (TIMI) implemented in Task-Based Learning (TBL) for the students with visual and auditory learning styles in performing writing of a recount text. To obtain the data, the research method of this study was quantitative by using 2x2 factorial experimental research design. The data collection was done by giving the VAK questionnaire and conducting the pre-test and the post-test. The data, then, was analyzed by using t-test and ANOVA. After doing the investigation, it was found that there was significant difference of the students performance in writing a recount text after learning by using IMIs. It means that the use of IMIs is effective. Then, there was an interaction between the implementation of TBL by using such media and the studentsâ learning styles in getting their writing performance. Even though, it did not give significant influence. Thus, it can be concluded that although the interaction among those variables did not give significant influence, the use of IMIs exactly made their learning result effective both for the students with visual and auditory learning styles.